Corporate responsibility and motivating corporate zakat payment / Siti Maziah Ab Rahman ...[et al.] - Ab Rahman, Siti Maziah; Setapa, Mariam; Abdul Wahid, Khalid; Rusli, Iman Nur Amirah; Nor Paizin, Muhsin; Abdul Wahab, and Mohd Hafeez Al-Amin (Universiti Teknologi MARA, 2021)
Zakat is one of the five pillars of the Islamic faith, which is an obligatory form of "charity", and every Muslim is expected to contribute. The use of zakat is not only to purify property but to purify the hearts of zakat payers from selfishness and wealth greed. Although it is part of Muslims obligation to pay zakat, the amount collected recorded is still lower and not optimal. The issue of zakat business payment is not often debated particularly on how to increase the number of business zakat payer. This is because zakat on wealth is more than total zakat on the busness. Malaysian zakat institution still faces several obstacles to increase the collection of business zakat. Most of the previous studies found that the zakat payer does not know about the basic foundations of zakat especially on business zakat payment. In addition, good leadership in zakat institutions may contribute to the efficiency and effectiveness of zakat funds and indirectly leads to an increase in corporate responsibility and motivating corporate zakat payment. Hence, the purpose of this research is to identify the relationship between the level of knowledge and the leadership of the institution zakat with corporate responsibility and motivating of corporate zakat payment. This research also used the Resource-Based View (RBV) theory. A qualitative method using an in-depth interview with a staff of Hotel Perdana Kota Bharu was applying in this study. The findings show that both were influenced corporate responsibility and motivating of corporate zakat payment.